The Morality of Markets. A Comment - Gregory Ponthiere; Nicolas Stevens (Global Labor Organization (GLO), 2024)
Dewatripont and Tirole (2024) defend the morality of markets on the ground of an irrelevance result: the social production of moral actions is independent from competitive pressure on markets. No matter how strong competitive pressure is, markets perform well in diffusing signals about moral values and in coordinating suppliers of moral actions. In this comment, we argue, on the contrary, that markets lead to a double crowding out of moral values: first, imperfect transmission of moral values on markets leads to an underproduction of moral actions despite the presence of highly ethical suppliers; second, competitive pressure on markets favors the eviction of highly ethical suppliers by less ethical suppliers.
Keywords: D21; D6; 330; competition; markets; morality; crowding out